Turning Territories into Temporalities: Three Aesthetic Methodologies - Giorgi, Gabriel Alejandro (2023)
The “new climate regime” forces thus a new understanding of the relations between the living and the extinct, and between the animate and the inanimate. This between is what our era interrogates so insistently: this is the quandary that shapes our investigations, our dreams and our terrors. Between life and non-life, between the living and the extinct: that threshold situates what we see recurring in our methodologies—the movements between the living and the ancestral. Ancestrality names these realms of existence that are irreducible to bios, and that still remain essential to life. Ancestral life, the ancestral dimension of the living (that opens lines of continuity with the dead and the extinct) is the figure that challenges so radically our understanding of both bios and geos, and that intersects our understanding of time.Turning territories into temporalities is, therefore, the practice to percolate, fissure, crack historical time with temporalities that are both irreducible to modern understanding of bios and its temporal deployment as modernity. What is at stake, then, is the very notion of life and its temporalities at the inflection when it can no longer be defined by its opposition to biological death.